Multilevel modeling and the explanatory autonomy of psychology - Fang, Wei. (Philosophy of The Social Sciences)
This article argues for the explanatory autonomy of psychology drawing on cases from the multilevel modeling practice. This is done by considering a multilevel linear model in personality and social psychology, and discussing its philosophical implications for the reductionism debate in philosophy of psychology. I argue that this practice challenges the reductionist position in philosophy of psychology, and supports the explanatory autonomy of psychology. - Reproduced
Keywords: Multilevel modeling, Psychology, Reductionism, Explanatory autonomy